Implementasi Projek Penguatan Profile Pelajar Pancasila Dimensi Mandiri di Sekolah Menengah Atas Negeri 1 Pecangaan Kabupaten Jepara - Muzakar, Kahar; YSH, AY Soegeng; Maryanto, Maryanto (PGRI Kota Semarang, 2024)
Implementing a project to strengthen the profile of Pancasila students as an effort to shape the character of students based on Pancasila values. Character formation does not start at school but must be instilled in children's daily lives from an early age, one of which is the character of independence. The focus of the research is 1) describing and analyzing the implementation planning for the Strengthening Pancasila Student Profile Project in the independent dimension. 2) describe and analyze the organization of the implementation of the Independent Dimension of the Pancasila Student Profile Strengthening Project. 3) describe and analyze the implementation of the Project for Strengthening the Profile of Pancasila Students in the independent dimension, and 4) describe and analyze the supervision of the implementation of the Project for Strengthening the Profile of Pancasila Students in the independent dimension at State Senior High School 1 Pecangaan, Jepara Regency. The research approach used is qualitative. This type of research is a case study. Qualitative research design through 1) pre-field or orientation stage, 2) fieldwork or focused exploration stage, 3) data analysis. Data collection techniques are interviews, observation and documentation. This research uses triangulation of sources and methods. Data analysis in three steps: data reduction, presenting data, and drawing conclusions. The research results show that: 1) planning for the implementation of the Independent Dimension Pancasila Student Profile Strengthening Project was carried out by the school principal including identifying needs, determining school programs, and socializing the program. 2) organizing the implementation of the Pancasila Student Profile Strengthening Project is carried out by the school principal including determining school resources, organizational development planning, assignment and delegation of authority. 3) the drive for the implementation of the Independent Dimension of the Pancasila Student Profile Strengthening Project is carried out by the school principal including the implementation of the P5 program, school infrastructure, direction of the school principal and motivation of the school principal. 4) supervision of the implementation of the Independent Dimension of the Pancasila Student Profile Strengthening Project is carried out by the school principal, including creating assessment instruments, evaluating implementation activities, and follow-up. The author suggests that school principals and teachers, as the main actors in this activity, must always collaborate starting from planning, implementation, to evaluation. Keywords: Implementation of the Pancasila Student Profile, Independent Character